Philosophy of care delivery for spina bifida - Thibadeau, Judy (Disabil Health J, 2019)
The multidisciplinary model (MCM) is described as one that utilizes skills and experience from practitioners belonging to various disciplines, each treating patients from a specific clinical perspective.(1) The Spina Bifida Association (SBA) supports and recommends that clinical care for people with Spina Bifida (SB) be provided in specialty clinics of which the MCM is an example; that care be coordinated; and that there be a plan for transitional care.(2) This paper explores the challenges the MCM faces with a transitioning and aging population in a care system that calls for a positive patient experience, engaged health care professionals, desired outcomes, with consideration of cost.